Review of the genus Anterhynchium de Saussure (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with the description of a new species and a key to the Oriental species - Dang, Hoa Thi; Tran, Duong Dinh; Nguyen, Anh Duc; Nguyen, Lien Thi Phuong (Zootaxa, 2025)
The solitary wasp genus Anterhynchium de Saussure, 1863 of Vietnam is reviewed. Four species are recognized, including A. conformalum Dang, Tran, AD Nguyen & Nguyen, sp. nov., which is described as new to science, based on both male and female specimens. This species was previously misidentified as A. flavomarginatum (Smith, 1852). The male genitalia of the other three species occurring in Vietnam, A. flavolineatum flavolineatum (Smith, 1857), A. mellyi (de Saussure, 1852), and A. punctatum Nguyen, 2015, are described and illustrated in details for the first time. A key is presented to the Oriental species of the genus. New locality records in Vietnam are presented for A. punctatum and A. f. flavolineatum. In addition, a new distribution record in China is reported for A. gibbifrons Yamane & Murota, 2015.